The Agatha Christie hour. Set 1 [videorecording (DVD)] - Kelsall, Freda; Corlett, William; Bowen, Trevor, 1941-; Simpson, Michael; Davis, Desmond, 1926-2021; Farnham, Brian; Christie, Agatha, 1890-1976; Nettles, John, 1943-; Grout, James, 1927-2012; Gaunt, William, 1937-; Denham, Maurice, 1909-2002 (Mystery! series., 2010)
"In these stories, lesser-known Christie heroes and heroines solve crimes of the heart as well as puzzling cases of larceny and murder. With just the right mix of danger and deception, romance and revenge, innocence and intrigue, these classic adaptations are Christie at her best"--Container.